QUALITY OF SERVICE AND PRICE PERCEPTION AFFECT CUSTOMER LOYALTY WITH CONSUMER SATISFACTION AS A MEDIATION VARIABLES - Margareta Evy da Silva (Journal of Applied Management and Business, 2020)
This study investigates the effect of service quality and perceived price on customer satisfaction and the effect of customer satisfaction on customer loyalty. This study also seeks to determine the mediating role of customer satisfaction on the relationship between service quality and price perceptions and customer loyalty. This study focuses on observations on 100 students in Sidoarjo who have made purchases at Indomaret-Sidoarjo. The research hypothesis testing adopted the Structural Equation Model-Partial Least Square (SEM-PLS) technique using SmartPLS. This study found that customer satisfaction has a significant effect on customer loyalty and perceived price also has a significant effect on customer loyalty. However, this research proves that service quality does not have a significant effect on customer satisfaction.